Human Papillomavirus Intermittence and Risk Factors Associated With First Detections and Redetections in the Ludwig-McGill Cohort Study of Adult Women - Talía Malagón; Helen Trottier; Mariam El‐Zein; Luisa L. Villa; Eduardo L. Franco; São Paulo; Maria Luiza Baggio; Lenice Galan; João Simão Sobrinho; José Carlos Mann Prado; Lara Termini; Cecília Costa; et al. (2023)
We assessed the incidence and risk factors for first detection and redetection with the same human papillomavirus (HPV) genotype, and prevalence of cytological lesions during HPV redetections.